Trabecular bone texture detected by plain radiography is associated with MRI-defined osteophytes in finger joints of women without radiographic osteoarthritis - Wolski, Marcin; Podsiadlo, Pawel; Stachowiak, Gwidon; Englund, M.; Haugen, I. (Elsevier, 2018)
Objective: To examine associations between trabecular bone (TB) texture and magnetic resonance imaging (MRI)-defined osteophytes in finger joints without radiographic osteoarthritis (OA) using an augmented variance orientation transform (AVOT) method. Design: In a cross-sectional study, associations of the TB texture and osteophytes were examined in 21 women with mean (standard deviation) age of 69.9 (5.3) from the Oslo Hand OA cohort. The AVOT was applied to distal and proximal TB regions selected on hand radiographs of the subjects. The regions were adjacent to 57 finger joints (24 distal and 33 proximal interphalangeal) without radiographic OA (Kellgren–Lawrence [KL] grade 0), without MRI-defined joint space narrowing (JSN), bone marrow lesions (BMLs), attrition, erosion, cysts, sclerosis, malalignment (all MRI grades 0) and without or only with mild synovitis (MRI grade 0 or 1). Bone texture parameters were calculated: mean fractal dimension (FDMEAN), FDs in the horizontal (FDH) and vertical (FDV) directions, and along the roughest part (FDSta). Associations between the parameters categorized into groups using tertiles and osteophytes were evaluated using logistic regression adjusted for age. Results: Lower FDSta and FDV in the distal TB regions were associated with increased odds of MRI-defined osteophytes (P < 0.037 for linear trend). No statistically significant associations were found for the proximal regions. Conclusions: Lower mean roughness and lower roughness in vertical and roughest directions of the proximal TB texture are associated with MRI-defined osteophytes in finger joints without radiographic OA. These findings suggest that TB texture may be a useful marker for detecting early hand OA.